2021
DOI: 10.1002/uog.22121
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal and infant outcome of fetuses with prenatally diagnosed hyperechogenic kidneys

Abstract: Renal outcome is good in isolated hyperechogenic kidneys, with 79% having normal renal function. Importantly, for prognostic counselling, all of the children in our non-selected series with isolated echogenic kidneys and normal amniotic fluid levels had normal renal outcome in infancy. What are the clinical implications of this work? Prenatal diagnosis of hyperechogenic kidneys allow early recognition and treatment of a renal disease in addition to counseling the family about the postnatal outcome and allow th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…Yulia et al 28 . recently summarized the characteristics and outcomes of 316 fetuses with hyperechogenic kidney.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yulia et al 28 . recently summarized the characteristics and outcomes of 316 fetuses with hyperechogenic kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Yulia et al 28 recently summarized the characteristics and outcomes of 316 fetuses with hyperechogenic kidney. They found that the majority of these cases had other associated defects.…”
Section: Discussionmentioning
confidence: 99%
“…20 In one study, fetuses with isolated HK and normal AF levels were found to have normal renal outcomes in infancy. 21 However, the long-term renal outcomes in such cases remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…If prenatal testing excludes genetic causes (i.e., all cytogenetic abnormalities, ARPKD, ADPKD, HNF1B ‐related disorder, tubular dysgenesis, and familial nephroblastoma), short‐term renal outcomes may be normal in the majority of isolated HK cases 20 . In one study, fetuses with isolated HK and normal AF levels were found to have normal renal outcomes in infancy 21 . However, the long‐term renal outcomes in such cases remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It provides an example of the variable clinical expressivity of an identical sequence variant in members of the same family. Therefore, a genetic test result must be correlated with clinical and sonographical findings as well as family history to aedequately counsel and care for the families [1,2]. This case highlights also the importance of a multidisciplinary approach.…”
mentioning
confidence: 97%